Strengthening agrifood systems through Living Labs: An overview of approaches across the Global South - Cavicchioli, Martina; Fisher, Monica; Snapp, Sieglinde (CIMMYT, 2026)
Living Labs have emerged as a promising approach to respond to wicked problems in agrifood systems. Notwithstanding the Western origins of the concept and the elevated number of Living Labs documented in Europe, the approach has emerged as critical to strengthening the socioeconomic resilience of Global South countries. Furthermore, its multistakeholder nature and cocreation principles make it a viable approach for the identification of locally-led solutions to contextual challenges. This study contributes to the existing Living Lab literature through an overview of different implementation approaches across the Global South. Drawing from the perspectives of researchers and practitioners, it aims to understand how the Living Lab approach is operationalized and to what extent implementers consider it effective at addressing emerging agrifood systems challenges in their respective countries or regions of intervention. Specifically, it enquires on the contribution of the Living Lab approach to the research infrastructure by looking at how stakeholders’ agency; data management; gender equality, youth, and social inclusion (GEYSI); and climate resilience are embedded, emergent, or absent within their operational logic. We use a mixed-methods approach that combines an online survey and semi-structured interviews with 14 participants working under seven different projects implementing a Living Lab approach or a closely related approach. For every project, we sampled one participant representing the overall project coordination perspective and another involved in the coordination of activities at country/regional level. Our findings show great diversity in implementation approaches both across our sample of projects and within the same projects. This diversity can be attributed to a range of factors, including funders’ orientation, the field of expertise of the leading organization, and implementers’ reinterpretation of the Living Lab approach. In alignment with other review of approaches in the Living Lab literature, this diversity provides evidence for the high adaptability of the Living Lab approach to a wide variety of settings and objectives. The following findings are reported on the different areas of focus of our study: • Stakeholder agencies: The involvement of different stakeholder groups varies between and within projects. The process of cocreation emerges as characterized by iterations between scientific and local knowledge, although stakeholders’ input varies significantly across the sample. Only some projects implement a specific governance approach in their Living Lab, while the possibility to minimize power imbalances within the group of stakeholders is generally considered difficult to achieve. • Data management: Most participants agree about the usefulness of data collected through a Living Lab for the communities, although data collection and sharing approaches differ significantly between projects. Some participants consider access to data as more critical compared to stakeholders’ direct involvement in the process of data collection and highlight the need for knowledge sharing platforms allowing circulation of knowledge and experiences across scales within (or beyond) the region of intervention. • Climate resilience and adaptation: Climate is considered an important concern within most projects. The unavailability of resources to track and monitor the effects of climate-smart innovations is highlighted as a challenge. It is also argued that the effectiveness of a Living Lab approach at strengthening communities’ resilience and adaptation to climate change is contingent on stakeholders’ commitment to the cause and on the priority attributed to climate objectives over other areas of focus. • GEYSI: Similarly, stakeholders’ different sensitivity towards gender equality, youth, and social inclusion influences the identification of objectives and implementation of activities. However, various participants consider the Living Lab approach as more effective at including views of marginal groups compared to other approaches used to inform agrifood systems’ interventions. • Advantages and challenges of a Living Lab approach: Overall, the multistakeholder and inclusive nature of Living Labs are highlighted as main strengths, while effectively mobilizing stakeholders and working under strict donor-funded projects are considered a challenge. While the range of implementation approaches documented in this overview does not allow for a unique characterization of Living Labs across the Global South, the experiences of implementers suggest that, within the framework of agricultural research for development, the Living Lab approach can effectively contribute to making the research infrastructure fairer and closer to the communities. We conclude by providing a few considerations derived from our participants’ experience that can offer some useful insights into a more sustainable and inclusive implementation of the approach, namely: (1) ensuring a Living Lab’s long-term sustainability; (2) discussing governance from the outset; (3) including marginalized groups in decision-making processes; and (4) the need for an inclusive, collaborative, and accessible knowledge sharing system.